2022
DOI: 10.3390/ijerph192316170
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Public Open Space on Older People’s Well-Being: From Neighborhood Social Cohesion to Place Dependence

Abstract: This quantitative study examines the effects of Public Open Space (POS) on older people’s well-being and examines the roles of neighborhood social cohesion (NSC) and place dependence (PD) as series buffers. A questionnaire survey of 501 people aged 65 and over was conducted in various communities of Hong Kong. Structural equation modelling (SEM) was used to analyze the pathways connecting POS and well-being. A multigroup analysis examined differences in the POS–well-being associations between the young-old (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 109 publications
1
8
0
1
Order By: Relevance
“…Kim et al examine the importance of neighborhood social cohesion in promoting healthy behaviors in older adults [36]. Table 11 show that the three factors in this study could effectively predict health behaviors, which was consistent with many other related studies [146,[148][149][150][151][152][153].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Kim et al examine the importance of neighborhood social cohesion in promoting healthy behaviors in older adults [36]. Table 11 show that the three factors in this study could effectively predict health behaviors, which was consistent with many other related studies [146,[148][149][150][151][152][153].…”
Section: Discussionsupporting
confidence: 85%
“…Social cohesion reduced the chances of taking up smoking, with positive effects on health behaviors [142][143][144]. It was also found that the stronger the social cohesion (sense of security and trust) of the older adults, the more likely they were to engage in exercise together, thus promoting health [126,145,146]. From the results of the group joint exercise, the older adults showed an active preference for exercising with others of the same age, as well as improved exercise compliance [147].…”
Section: Discussionmentioning
confidence: 98%
“…It is also an element of the built environment that may foster a sense of community by facilitating chance encounters between neighbors (Talen, 2000;Low et al, 2005). Therefore, the public open spaces that are associated with natural elements and other features could become places that can promote social interactions and social cohesion among the community in cities and neighborhoods (Jenning, 2016;Boessen, 2018;Badar and Bahadure, 2020;Chen and Seo, 2022). Thus, community participation in public open space planning is crucial to producing good public spaces for the community.…”
Section: Introductionmentioning
confidence: 99%
“…Different spatial patterns and living styles trigger different feelings, inducing specific psychological feelings in older adults, which can be conducive to their exploration of new environments, which in turn affects their behavioral patterns. Chen Shi et al, through a questionnaire survey of older adults, reported that the relationship between open public space and emotional well-being was stronger than that between social and psychological well-being [12]. Sohyune et al studied health behaviors, depression, and life satisfaction among older adults in rural Korea [13].…”
Section: Introductionmentioning
confidence: 99%